Assessment of Quality of Life Studies of Renal Failure patients in different cities of Punjab, Pakistan - Nazish Munawar, Muhammad Usman, Yasir Hussain, Qurat Ul Ain, Irfan Elahi, Tariq Ali, Muhammad Irfan Jamil (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the quality of life (QOL) of renal failure patients on maintenance hemodialysis on the basis of their baseline characteristics in Lahore, Pakistan. Study design: A cross sectional study was carried out with two hundred and ten patients selected randomly from dialysis centers in General, Mayo and Jinnah hospitals, Lahore Pakistan, to measure and analyze the QOL of hemodialysis patients by pre-validated KDQOL-SFTM version 1.3 in English language. Methodology: Interviews of the patients were performed to collect data. SF-36 items mean and standard deviation were performed to analyze data on the basis of gender and age groups. Results: Among the eleven scales targeting End-Stage Renal Disease (ESRD), only the "Effects of Kidney Disease" scale demonstrates a greater impact on males than females. However, three scales including Symptom/Problem list, Quality of Social Interaction, and Dialysis Staff Encouragement show suboptimal results in young patients. Similarly, two of the seven health-related outcome scales, Physical Functioning and Energy Fatigue, exhibit poor outcomes in young patients. Conclusion: Major cause of their kidney disease was hypertension and diabetes. Overall, less number of prescribed medications, decreased hospitalization and reduced hospital visits are the factors showing overall better quality of life.This study helps us understand the impacts of kidney disease on different genders and age groups, guiding the development of personalized care plans. Keywords: Quality of life (QOL), End stage renal disease ESRD, hemodialysis, KDQOL-SFTM version 1.3